Screening and Isolation of Cyclodextrin Producing Fungi and Bacteria From Selected UNIMAS AAS Collection - Kathleen, Michelle Mikal (Universiti Malaysia Sarawak (UNIMAS), 2010)
Cyclodextrin (CD) is cyclic oligosaccharides consisting of α-1,4-glucosidic linkage produced by the reaction of cyclodextrin glycosyltransferase (CGTase EC 2.4.1.19) and starch. CGTase are usually produced by bacteria mostly from the Bacillus genera. There is no research done on fungi for production of CD. In this study, screening was done on fungi and bacteria to identify which fungi and bacteria could produce CGTase that will later form CD. The screening was done on the Horikoshi II media containing phenolphthalein and methyl orange as CGTase indicator. Five fungi and three bacteria from the AAS UNIMAS collection were screened. Screening and enzyme assay showed that two fungi, Aspergillus nomius and Aspergillus flavus produce CGTase. Both fungi have high enzyme activity with 12.97U/ml for A.nomius and 10.66U/ml for A.flavus based on CGTase assay.